Angry conversations with God : a snarky but authentic spiritual memoir - Isaacs, Susan E. (New York : Faith Words, 2011)
"A spiritual memoir about a middle-class white girl's dark night of the soul from comedian and skeptical Christian Susan Isaacs"--Provided by the publisher.
Getting God on the Couch -- The Nice Jesus on Every Wall -- My Two Dads -- Cheating on Jesus -- We've Only Just Begun -- The Hokey Pokey for Oakies -- Rock 'n' Roll Slackers 4 Jesus -- Awaken the Giant Hormone Within -- Breaking Up over Dentistry -- Bottoms Up -- New Lease, New Life, New York -- Mostly Mister Right -- A Father's Valediction -- My Own Private September 11 -- God's Scorched-Earth Policy -- Middle-Class White Girl's Dark Night of the Soul -- Nobody's Fault but My Own -- For Fun and for Free -- The Best Thing That Ever Happened to Me.
Keywords: Isaacs, Susan E; Lutheran women -- United States -- Biography; Lutherans -- United States -- Biography; Spiritual biography -- United States; Middle class women -- United States -- Biography; Women, White -- United States -- Biography; Midlife crisis; Women comedians -- United States -- Biography; Comedians -- United States -- Biography; United States; Biography